Optimizing the Amount of Production Using Hybrid Fuzzy Logic and Census II - Susana Limanto; vincentius Riandaru Prasetyo; Mirella Mercifia (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2023)
Companies should do planning before the production process. Production planning is expected to avoid excessive or insufficient product stocks that harm the company. This study aims to help a plastic spoon company in Gresik, East Java to determine the optimal amount of production using the Fuzzy method. The input variables used are the amount of demand and supply. However, the amount of demand that fluctuated, especially during the Covid-19 pandemic, made it difficult for the company to estimate the amount of demand in the upcoming production period. Therefore, in this study, the amount of demand is calculated from the results of forecasting with the Cencus II method. The results of the study provide an accuracy of the recommendations for the amount of production of 77% and an accuracy of forecasting results of 82%.